The effects of cyber fraud on higher education financial aid students in South Africa - Hutchinson, Gershon (Department of Information Systems, 2025)
Due to the exponential growth of the internet, cyber fraud has become an increasingly prevalent issue globally, and South Africa is no exception. Financial aid is critical to enabling higher education for many South African students, particularly those from disadvantaged backgrounds. The NSFAS has repeatedly cautioned students regarding fraudsters using a variety of techniques, including phishing, vishing, spoofed websites, and social media, which criminals employ to access their allowances. Yet, cyber-crime, particularly cyber fraud continues to infiltrate the higher education sector and many others in South Africa. Understanding the unique challenges faced by South African higher education financial aid students concerning cyber fraud is essential for developing preventive strategies and providing support. It is crucial to understand the effect of cyber fraud on these students, as cyber fraud can severely affect their educational opportunities and well-being. The goal of this study is to identify and understand how South African higher education financial aid students perceive cyber fraud; and how cyber fraud affects them. The study employed a qualitative research design and utilized purposive and snowball sampling techniques to select participants. A semi-structured interview instrument, informed by existing academic literature, guided the conversation. Thirty active semi-structured interviews were conducted with students affected by cyber fraud to gain a comprehensive understanding of the topic. Inductive thematic analysis was employed for data analysis. Patterns in the data were identified, grouped to form overarching themes. The findings show that all participants in this study experienced financial losses. The study found that 90% of participants had no formal or informal training on cyber fraud. The data suggests that most students lack the knowledge and skills to identify and protect themselves against fraudulent activities. Sixty-two percent of participants reported that the cyber fraud had a negative effect on their education, with 27% confirming that it affected their grades and 35% dropping out of school. The study found that some victims coped better than others, with those having financial or emotional support recovering more easily. The findings underscore the urgent need for training and awareness programs tailored explicitly for financial aid students, particularly those receiving financial aid for the first time. Beyond the immediate financial losses, the study also highlights the psychological, emotional, behavioural, and secondary affects experienced by affected students. It underscores the crucial role of support systems in determining students' academic success. Future research could explore the most effective methods for delivering training and awareness programs to financial aid recipients to protect them from cyber fraud.